Recent advances in the treatment of systemic sclerosis associated interstitial lung disease - Kamenova, Antoniya; Tzouvelekis, Argyris; Margaritopoulos, George A. (Frontiers in Medicine, 2023)
Connective tissue diseases (CTDs) are a heterogenous group of systemic inflammatory disorders. The development of connective tissue disease-associated interstitial lung disease (CTD-ILD) is a key complication associated with significant morbidity and mortality. The aim of this review is to explore the pathogenesis of CTD-ILD and summarize the recent evidence from clinical trials for novel treatment options, including the role of antifibrotics and immunomodulatory therapies with a focus on systemic sclerosis associated ILD. Further clinical trials are ongoing to explore combination therapies and more targeted therapeutic options. Clinicians remain faced with the difficult challenge of appropriately selecting patients who will benefit from the available therapies and timing the start of therapy at the most suitable part of the disease course.